Direct evidence for opposite effects of D-glucose and D-glyceraldehyde on cytoplasmic pH of mouse pancreatic beta-cells. - Arkhammar, P; Berggren, P; Rorsman, P (Kluwer Academic Publishers-Plenum Publishers, 1986)
The effects of D-glucose, D-glyceraldehyde, glibenclamide, D-600, NH4+ and high concentrations of K+ on cytoplasmic pH (pHi) were investigated in dispersed and cultured pancreatic beta-cells from ob/ob mice. The cytoplasmic pH was measured with the fluorescent H+-indicator quene 1. The average pHi value in resting beta-cells was 6.71. Addition of 20 mM of the physiological stimulus D-glucose increased pHi with 0.05 units. Both glibenclamide and high concentrations of K+ decreased pHi. The latter effects were completely reversed by D-600, supporting the notion that free cytoplasmic Ca2+ can be involved in the regulation of pHi. In contrast to D-glucose, 10 mM of D-glyceraldehyde decreased pHi by 0.09 units, an effect persisting even in the presence of D-600. From the present study it is evident that D-glyceraldehyde and D-glucose have opposite effects on pHi in pancreatic beta-cells.